Distance learning tools for the development of foreign language communicative competence - Kokorina, Lyudmyla V.; Potreba, Nadiia A.; Zharykova, Maryna V.; Horlova, Olena V. (Linguistics and Culture Review, 2021)
The primary feature of modernity is the dynamic development of information technology. Students must be taught the way to select and find useful information for a particular educational task from the start. The development of this skill is based on the various learning strategies. Thus, the strategies that contribute to the development of autonomy is a crucial aspect in the process of language learning supported by the tools of modern digital technology. Distance learning, video conferencing systems, telecollaboration are technological advancements that require a new paradigm for their usage. Both asynchronous and synchronous distance learning have already become part of nowadays reality. Thus, it is difficult to question the effectiveness of this form of learning and knowledge acquisition even though there is still a lack of the "infrastructure" to take advantage of new technologies to the fullest. The subject of the article is to reflect the use of distance learning in language education. A description of empirical research was made based on the method of distance learning in linguistic education, which main goal was to assess the effectiveness and analysis of features of the distance method for studying/learning foreign languages.